Synura ehrenbergii sp. nov. (Chrysophyceae, Synurales), a new species from Russia - Shadrina, Svetlana N.; Safronova, Tatiana (Phytotaxa, 2026)
A new species, Synura ehrenbergii sp. nov., from Russia is described based on scale morphology studied by means of transmission and scanning electron microscopy. This species belongs to the section Peterseniae, and it has three types of scales with a central keel: apical scales, oval body scales, and narrow rear scales. All scales are covered with an external siliceous layer, which is clearly visible in SEM. Synura ehrenbergii was found in plankton samples taken from two lakes in the Nature Park Vepssky Les, Northwestern Russia.